2015
DOI: 10.1002/cpt.205
|View full text |Cite
|
Sign up to set email alerts
|

Late sodium current block for drug‐induced long QT syndrome: Results from a prospective clinical trial

Abstract: Drug-induced long QT syndrome has resulted in many drugs being withdrawn from the market. At the same time, the current regulatory paradigm for screening new drugs causing long QT syndrome is preventing drugs from reaching the market, sometimes inappropriately. In this study, we report the results of a first-of-a-kind clinical trial studying late sodium (mexiletine and lidocaine) and calcium (diltiazem) current blocking drugs to counteract the effects of hERG potassium channel blocking drugs (dofetilide and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
144
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(165 citation statements)
references
References 38 publications
12
144
1
Order By: Relevance
“…It is important to recognize that this was a retrospective analysis and for the majority of the drugs the ion channel information was incomplete. These limitations were, however, addressed by two recent prospective clinical studies sponsored by the FDA [30,31], which confirmed the findings of the retrospective study.…”
Section: Alternatives To Qt As a Biomarkersupporting
confidence: 73%
“…It is important to recognize that this was a retrospective analysis and for the majority of the drugs the ion channel information was incomplete. These limitations were, however, addressed by two recent prospective clinical studies sponsored by the FDA [30,31], which confirmed the findings of the retrospective study.…”
Section: Alternatives To Qt As a Biomarkersupporting
confidence: 73%
“…The IC 50 values of the human ether-à-go-go-related gene (hERG) K + channel have been reported to be 7.2-10.7 for disopyramide, 262.9 for lidocaine and 3.9 μmol/L for flecainide at 35-37ºC (Polak et al, 2009), which may partly explain the difference in the extent of prolongation of field potential duration. It should be noted that the result for lidocaine was directionally different from that in the in situ human heart, in which the QT interval was shortened via late Na + current inhibition (Johannesen et al, 2016). Thus, the constitutively active late Na + current may be hardly expressed in the cell sheet unlike the human heart.…”
Section: Effects Of Na + Channel Blockers On the Electrophysiologicalmentioning
confidence: 85%
“…When incorporated into the ORd model, action potential waveforms and electrical behaviors were also faithfully reproduced.The second challenge was to develop and characterize a set of candidate metrics that could distinguish different levels of TdP risk. While standardized patch clamp protocols and new multi-channel pharmacology data sets were being generated by the ICWG, initial in silico efforts used IC 50 s for the various cardiac ion channels of interest from the patch clamp data set generated byCrumb et al (2016) and combined with dynamic hERG block data generated by the ICWG using manual patch clamp methods at both room and physiological temperatures. The utility of the classical risk metrics, such as APD90, triangulation of the action potential waveform, and the appearance of early after depolarizations (EADs), were evaluated, along with more biophysical measurements associated with action potential prolongation and torsadogenesis, such as net repolarizing current and the likelihood and degree of drug trapping within the hERG/I Kr channel.…”
mentioning
confidence: 99%